Biomineralization-inspired crystallization of monodisperse α-Mn2O3 octahedra and assembly of high-capacity lithium-ion battery anodes. Issue 13 (13th March 2017) - Henzie, Joel; Etacheri, Vinodkumar; Jahan, Maryam; Rong, Hongpan; Hong, Chulgi Nathan; Pol, Vilas G.
Abstract : Uniform colloidal building-blocks enable the creation of more stable, structurally sophisticated materials. Abstract : Uniform colloidal building-blocks enable the creation of more stable, structurally sophisticated materials. Here we describe a simple polymer-mediated approach to generate grams of monodisperse, single-crystal α-Mn2 O3 nanocrystals bound by 111 facets. The technique is inspired in part by biomineralization, where organisms use macromolecular matrices or compartments to trigger the oriented nucleation and growth of crystalline phases. Polyvinylpyrrolidone (PVP) behaves as a polymeric nano-reactor by coordinating to the manganese (Mn) precursor while recruiting the NO x oxidizing agent from solution to drive the co-precipitation of the manganese oxide. PVP also serves as a molecular template to guide the nucleation of trigonal bipyramids composed of Mn3 O4 . The porosity of the Mn3 O4 particles indicates that they form non-classically via oriented attachment instead of atom-by-atom. The particles are further oxidized and transform into single-crystal α-Mn2 O3 octahedra. This co-precipitation approach is advantageous because it can generate large amounts of monodisperse nanocrystals at low economic cost. α-Mn2 O3 is an alternative lithium ion battery (LIB) anode material that is earth abundant and has ∼2.7 times higher capacity than conventional graphite anodes. We assembled the monodisperse α-Mn2 O3 octahedra into LIB anodes to examine their performance in a realistic device. The α-Mn2 O3 octahedra exhibit good rate performance, cycling stability, coulombic efficiency and morphology retention during extended lithiation–delithiation cycles compared to previous reports for this material. We attribute the improved electrochemical performance of the α-Mn2 O3 octahedra to the lack of agglomeration in the uniformly distributed electrode and improved lithiation of single crystalline α-Mn2 O3 nanoparticles.